Elliptical sentences in Azerbaijan Turkish with elliptical context - ELZA ALIŞOVA DEMİRDAĞ (Uluslararası Türk Lehçe Araştırmaları Dergisi, 2022)
Elliptic is a language phenomenon that leaves some language units in a deep structure in written and oral expression within the framework of the rules of that language. While writing or speaking, various declensions are made in the language for reasons such as adding vitality to the speech, ensuring fluency, avoiding repetition, saving, and emphasizing. The ellipsis, which is called by various terms such as memorizing, ellipsis, declension, abbreviation, zero repetition, and ellipse, appears in Turkey Turkish in terms of phonology, morphology, syntax, and provides a wide range of studies from sound to sentence. In this study, the subject of ellipsis in the sentence in Azerbaijani Turkish will be discussed. This language phenomenon, which is called elliptic sentence in Azerbaijani Turkish, is explained as "like an ellipse, in the form of an ellipse, depending on the reduction of the easily understood word in the sentence". Elliptical sentences with half sentence status, which can be used independently, are a type of sentence that allows the speaker to explain more opinions by using fewer words. Half and elliptical sentences, which are examined in half sentences, are the reduction of the verb in written and oral expression. Dropping the verb comes in two ways: 1. Text-based drop, 2. Elliptical drop. In textual reduction, the reduction of the verb depends on the text and is dropped to avoid repetition. In such sentences, it is possible to replace the abbreviated verb according to the previous sentences of the text. The other type of semilunar sentences with reduced verbs is elliptic sentences. The verb dropped in elliptical half sentences is determined not according to the text, but according to the elements and meaning of the sentence itself. In this context, while there is no use of outside the text in the text-based drop, elliptical sentences are used independently.